1998
DOI: 10.1007/s004210050326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intense interval workouts on running economy using three recovery durations

Abstract: This manuscript has been reproduced from the microfilm master. UMI films the text directly from the original or copy submitted. Thus, sorne thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer.The quality of tbis reproduction is dependent upon tbe quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
9
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 73 publications
5
9
1
2
Order By: Relevance
“…In our study the baseline _ V O 2 in EX-90 did not return to its original level indicating that there was an additional O 2 cost at the start of EX-90. Consistent with the hypothesis of a decrease in mechanical eciency, an increase in _ V O 2 during cycling and running of low and moderate intensity has been observed after prior high-intensity exercise and rests of 5±10 min (Davis and Gass 1981;Zavorsky et al 1998). It can be hypothesised that the increase in the 3rd min _ V O 2 of EX-90 re¯ected the decrease in mechanical eciency, already present during unloaded cycling, and that the expected increase in the end _ V O 2 was oset by the lowering eect on the _ V O 2 slow component with the net result being a not signi®cantly changed end _ V O 2 .…”
Section: Discussionsupporting
confidence: 78%
“…In our study the baseline _ V O 2 in EX-90 did not return to its original level indicating that there was an additional O 2 cost at the start of EX-90. Consistent with the hypothesis of a decrease in mechanical eciency, an increase in _ V O 2 during cycling and running of low and moderate intensity has been observed after prior high-intensity exercise and rests of 5±10 min (Davis and Gass 1981;Zavorsky et al 1998). It can be hypothesised that the increase in the 3rd min _ V O 2 of EX-90 re¯ected the decrease in mechanical eciency, already present during unloaded cycling, and that the expected increase in the end _ V O 2 was oset by the lowering eect on the _ V O 2 slow component with the net result being a not signi®cantly changed end _ V O 2 .…”
Section: Discussionsupporting
confidence: 78%
“…time trials and/or interval training sessions) in an attempt to maximise training adaptations. High-intensity interval training (HIIT) has been shown to result in acute decreases in running economy, an elevated exercising heart rate and an altered hormonal profile (Vuorimaa et al 1999;Zavorsky et al 1998). Furthermore, in the days following HIIT, leg power is reduced, whilst blood creatine kinase (CK) levels, rating of perceived exertion during constant paced running and symptoms of fatigue have been shown to be elevated (Fry et al 1991;Robson-Ansley et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…[mean = 196 (SD 13), range = 166 to 232 mL/kg/km] (Zavorsky, Montgomery, & Pearsall, 1998). These findings are similar to other research by Morgan et al, who found the variation of RE is about 1.3% (range = 0.3 to 4.4%) in well trained runners (Morgan, Martin, Krahenbuhl, & Baldini, 1991).…”
Section: Day-to-day Variability In Resupporting
confidence: 88%